Analisa model utaut (unified theory of acceptance and use of technology) dalam peningkatan penggunaan layanan transaksi digital Bank Mandiri pada masa pandemi covid-19 - Usman, Teuku Ali (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The journal aims to explain the research on increasing users of digital banking transaction services, namely Mandiri Online / New Livin by Mandiri during the COVID-19 pandemic using the Unified Theory of Acceptance and Usage of Technology (UTAUT) model and quantitative research methods with surveys conducted to 300 respondents in the West Jakarta Trade Cluster area. The results of the research are in the form of identifying factors that have a positive correlation with increasing the use of Mandiri Online / New Livin during the COVID-19 pandemic so that they can be used as guidelines for taking